Substructure in the Frontier Fields from weak lensing flexion. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Rexroth, Markus
Abstract: Flexion is the second order weak gravitational lensing effect responsible for the arclike appearance of sources. It is highly sensitive to dark matter substructure and can greatly increase the resolution of mass maps, but it is very hard to measure. We present an automated flexion measurement pipeline for Hubble Space Telescope data and a preliminary application to the Frontier Fields cluster MACSJ0416.1-2403.